2011
DOI: 10.1186/1756-6606-4-29
|View full text |Cite
|
Sign up to set email alerts
|

Fetal alcohol exposure leads to abnormal olfactory bulb development and impaired odor discrimination in adult mice

Abstract: BackgroundChildren whose mothers consumed alcohol during pregnancy exhibit widespread brain abnormalities and a complex array of behavioral disturbances. Here, we used a mouse model of fetal alcohol exposure to investigate relationships between brain abnormalities and specific behavioral alterations during adulthood.ResultsMice drank a 10% ethanol solution throughout pregnancy. When fetal alcohol-exposed offspring reached adulthood, we used high resolution MRI to conduct a brain-wide screen for structural chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 89 publications
3
49
1
Order By: Relevance
“…The apparent resilience of the adult NSC pool to in vivo alcohol exposure contrasts in some respects with recent findings indicating that prenatal alcohol reduces the number of neurospheres in the neonatal SVZ (Akers et al, 2011; Rubert et al, 2006; Santillano et al, 2005). NSCs may be more sensitive to insults during embryonic expansion of the pool relative to the static population dynamics of adulthood, as has been demonstrated for other insults such as prenatal versus adult stress (Kippin et al, 2004).…”
Section: Discussioncontrasting
confidence: 85%
“…The apparent resilience of the adult NSC pool to in vivo alcohol exposure contrasts in some respects with recent findings indicating that prenatal alcohol reduces the number of neurospheres in the neonatal SVZ (Akers et al, 2011; Rubert et al, 2006; Santillano et al, 2005). NSCs may be more sensitive to insults during embryonic expansion of the pool relative to the static population dynamics of adulthood, as has been demonstrated for other insults such as prenatal versus adult stress (Kippin et al, 2004).…”
Section: Discussioncontrasting
confidence: 85%
“…Ex vivo MRI at PD60 following PAE (10% v/v) throughout gestation revealed both increases and decreases in regional brain volumes in the offspring of 129Svev and C57Bl/6 mice, including decreased volumes of the olfactory bulbs, the granule cell layer of the dentate gyrus and the fourth ventricle; and increased volumes of the basal forebrain, the posterior part of the anterior commissure, the stria medullaris of the thalamus and the amygdala [166].…”
Section: Rodent Models Of Chronic Moderate Dose Of Paementioning
confidence: 99%
“…We found no differences between groups in dam body weight at onset of pregnancy (control: 26.8 + 1.4 g, EtOH: 25.6 + 0.7 g), weight gained across pregnancy (control: 12.7 + 1.2 g, EtOH: 13.9 + 0.6 g), or litter size (control: 6.0 + 0.6 pups, EtOH: 6.7 + 0.4 pups). Previous studies have shown that this procedure has no effect on maternal behavior or pup body weight but produces changes in brain volume, levels of neurotrophic factors, and behavior that persist into adulthood (Allan et al 2003;Caldwell et al 2008;Akers et al 2011). …”
Section: Fetal Alcohol Exposurementioning
confidence: 99%
“…The fetal alcohol exposure procedure was adapted from previous studies (Allan et al 2003;Akers et al 2011). Briefly, female mice (n ¼ 10) were given saccharin-flavored drinking water (0.1% saccharin) to which ethanol (EtOH) was gradually introduced (0% EtOH for 4 d, 2% EtOH for 1 d, 5% for 1 d, 10% for 4 d).…”
Section: Fetal Alcohol Exposurementioning
confidence: 99%